REMOVAL OF ZINC FROM AQUEOUS SOLUTION USING COFFEE INDUSTRY WASTE - K. KUMARASWAMY,; B.V. DHANANJANEYULU,; P.VIJETHA,; M. SIVA JAGADISH KUMAR, (International Journal of Pharma and Bio Sciences, 2014)
Biosorption is most economical method for removing toxic metals from waste water.The paper presents the results of studies carried out on sorption of zinc ions from aqueous solutions by a coffee industry waste s a low-cost sorbent. It was found that crushed coffee industry waste possess relatively high sorption capacity as 46.05 mg/g, when comparing with other sorbents. The biosorption studies were determined as a function of initial metal ion concentrations, pH, biosorbent dosage and biosorbent particle size. About 0.1g of coffee industry waste was found to be enough to remove 71.66% of zinc for 20 mg/L of metal ion concentration from 30 mL aqueous solution. The optimum pH value was found to be 7. The experimental equilibrium data were tested with the biosorption isotherms like Langmuir, Freundlich and their equilibrium parameters were determined. The best-adjusted model to the experimental equilibrium data for coffee industry waste was the Freundlich model